2022
DOI: 10.3390/ruminants2040029
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Growth Hormone Exon-5 Polymorphism on Growth Traits, Body Measurements, Slaughter and Carcass Characteristics, and Meat Quality in Meat-Type Lambs in Turkey

Abstract: This study examined the relationship between GHE5 polymorphisms and growth and carcass characteristics of meat-type sheep breeds reared in Turkey. A total of 202 lambs were tested, consisting of five breeds. By SSCP analysis and nucleotide sequencing, 14 nucleotide changes (12 substitutions and two deletions) were identified in four variants of GHE5. In the coding region of GHE5, five substitutions occur, including c.1588C>Y(C/T) (Ala160Val), c.1603A>M(A/C), c.1604G>S(G/C) (Lys165Thr), c.1606A>W(A/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
0
1
Order By: Relevance
“…In contrast to our observations, Pandya et al (2021) found that at six months of age, goats with BB genotypes had a superior body mass (P < 0.05) than those with AB genotypes in Surti Goats Singh et al (2015). observed similar ndings for body length in Sirohi and Barbari goats across all ages; however, statistical analysis failed to reveal signi cantly differ The same ndings were reported byEsen and Elmac (2022), who found that yearling lambs with the P1 variant of the growth Hormone Exon-5 (GHE5) gene have a higher body length (BL), wider leg girth, and lean cannon bone periphery (CBP) (P > 0.05), in comparison to lambs with the other variant (P2), whose body length is shorter and CBP is thicker Selionova et al (2022). revealed a favourable connection between the molecular marker among MSTN, HEG1, FGF10, FGF14, GHRH, and SLAIN genes linked to live body mass at age four months old.…”
contrasting
confidence: 87%
“…In contrast to our observations, Pandya et al (2021) found that at six months of age, goats with BB genotypes had a superior body mass (P < 0.05) than those with AB genotypes in Surti Goats Singh et al (2015). observed similar ndings for body length in Sirohi and Barbari goats across all ages; however, statistical analysis failed to reveal signi cantly differ The same ndings were reported byEsen and Elmac (2022), who found that yearling lambs with the P1 variant of the growth Hormone Exon-5 (GHE5) gene have a higher body length (BL), wider leg girth, and lean cannon bone periphery (CBP) (P > 0.05), in comparison to lambs with the other variant (P2), whose body length is shorter and CBP is thicker Selionova et al (2022). revealed a favourable connection between the molecular marker among MSTN, HEG1, FGF10, FGF14, GHRH, and SLAIN genes linked to live body mass at age four months old.…”
contrasting
confidence: 87%